Methanol a sustainable transport fuel for SI engines - Agarwal, Avinash Kumar; Valera, Hardikk; Pexa, Martin; Cedík, Jakub (Energy, environment, and sustainability, 2021)
This monograph focuses on methanol and its utilization in transportation sector, namely in spark ignition (SI) engines. The contents focus on methanol production and presents a variety of production technologies from different feedstocks. The potential of methanol utilization in transportation in SI engines is discussed, its challenges, limitations, aspects related to its utilization and current global use of methanol are also presented. The book also contains chapters related to pollutant formation and exhaust emissions from methanol fuelled SI engines, one chapter is focused specifically on formaldehyde emissions, which possesses one of the greatest challenges of methanol use in IC engines. Readers will learn about the production aspects of methanol, its potential as a sustainable fuel, its utilization in SI engine and the effect of methanol and its utilization techniques on engine performance, combustion, exhaust emissions, efficiency and other important parameters. This volume will be a useful guide for professionals, post-graduate students involved in alternative fuels, spark ignition engines, and environmental research